Chapter Searching for 'Italianità' in the Dodecanese Islands (1912-1943). Some Considerations on Art, Architecture and Archaeology through the Works of Hermes Balducci - ORLANDI, LUCA (Connessioni. Studies in Transcultural History, 2022)
The rediscovery and promotion of fourteen islands in the Aegean Sea - renamed the Dodecanese Islands - annexed to Italy as a military possession while formally under the dominion of the Ottomans, might be considered another phase in the search for an Italian identity. From 1912 to 1943 these islands experienced Italy's ambiguous presence as invaders and colonizers. This paper aims to highlight the concept of Italianità through the works of Hermes Balducci, one of the protagonists of Italian colonial architecture in the Dodecanese Islands. To this end and using lesser-known material, this case study intends to recreate and redefine the past of the Italian presence on these islands and provide an interesting point of view in the search for a lost and rediscovered Italian spirit.